Non-invasive assessment of volume status of children with edema due to steroid sensitive nephrotic syndrome using urinary indices and inferior venacava ultrasonography - Kalyani Pillai; Jalaludeen, Jawhara; Vadakoot Krishnan Parvathy (Asian Journal of Medical Sciences, 2023)
Background: It is clinically difficult to assess the intravascular volume status of children with edema in nephrotic syndrome. This makes decision-making challenging, regarding the use of diuretics or albumin infusion in the management of edema. Ideally, hormonal assay and central venous pressure monitoring are accurate but difficult to do as these methods are invasive and expensive to be applied to every child presenting with edema of nephrotic syndrome. Hence, the need for reliable non-invasive investigations to assess the volume status of children with edema. Aims and Objectives: The aim of the study was to assess the volume status of children with edema due to steroid sensitive nephrotic syndrome using noninvasive methods such as urinary indices (Fractional excretion of sodium (FeNa) and urine Potasium index (K index)) and inferior venacava diameter (IVCD) by ultrasonography and to determine the association between them. Materials and Methods: In this analytical cross-sectional study, 82 subjects fitting the inclusion criteria were included in the study. FeNa, K index and IVCD were determined. The volume status was assessed and association between the three calculated (Fischer exact test). Results: Out of 82 children, 56.1%, 68.3%, and 63.5% based on FeNa, K index, and IVCD respectively were having hypervolemic volume status. There is a statistically significant association between FeNa and K index and between urinary indices and IVCD. Conclusion: The present study supports the overfill hypothesis of edema formation. IVCD like urinary indices is a non-invasive and reliable investigation to determine volume status in nephrotic child with edema.